2019
DOI: 10.1016/j.ultrasmedbio.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Measurement of Tongue Movement During Respiration: Comparison Between Ultrasonography and Magnetic Resonance Imaging

Abstract: The tongue makes up the anterior pharyngeal wall and is critical for airway patency. Magnetic resonance imaging (MRI) is commonly used to study pharyngeal muscle function in pharyngeal disorders such as obstructive sleep apnoea. Tagged MRI and ultrasound studies have separately revealed »1 mm of anterior tongue movement during inspiration in healthy patients, but these modalities have not been directly compared. In the study described here, agreement between ultrasound and MRI in measuring regional tongue disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…The tongue moves anteriorly during inspiration to open the airway and moves posteriorly during expiration to return to the original UA caliber while keeping the airway open. Previous studies comparing the tagged MRI and an automated US tracking algorithm (Kwan et al, 2014, 2015) confirmed the respiratory‐related tongue motions (Kwan, Juge, Gandevia, & Bilston, 2019). To minimize the effect of respiratory phases on tongue movement, we began acquiring the US image sequences while the participants were in an end‐expiration phase (a pause) of quiet breathing.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The tongue moves anteriorly during inspiration to open the airway and moves posteriorly during expiration to return to the original UA caliber while keeping the airway open. Previous studies comparing the tagged MRI and an automated US tracking algorithm (Kwan et al, 2014, 2015) confirmed the respiratory‐related tongue motions (Kwan, Juge, Gandevia, & Bilston, 2019). To minimize the effect of respiratory phases on tongue movement, we began acquiring the US image sequences while the participants were in an end‐expiration phase (a pause) of quiet breathing.…”
Section: Discussionmentioning
confidence: 77%
“…Upper panel: tongue area differences between non-OSA and OSA groups during normal breathing (a), Mueller maneuver (b), and the differences between normal breathing and Mueller maneuver (c). Lower panel: maximum tongue thickness between non-OSA and OSA groups during normal breathing (d), Mueller maneuver (e), and the differences between normal breathing and Mueller maneuver (f) (Kwan et al, 2014(Kwan et al, , 2015 confirmed the respiratory-related tongue motions (Kwan, Juge, Gandevia, & Bilston, 2019). To minimize the effect of respiratory phases on tongue movement, we began acquiring the US image sequences while the participants were in an end-expiration phase (a pause) of quiet breathing.…”
Section: F I G U R Ementioning
confidence: 84%
“…Ultrasound measurements of the posterior tongue displacement were 0.24±0.64 mm greater than MRI measurements (95% limits of agreement: 1.03 to -1.49). The study concluded that ultrasound was a suitable method for measuring tongue movements (45).…”
Section: Clinical Significancementioning
confidence: 98%
“…; Kwan et al . ). Previous studies of the human upper airway indicated that the posterior region of the tongue moves anteriorly during inspiration resulting in airway dilatation (Cheng et al .…”
Section: Introductionmentioning
confidence: 97%
“…It allows dynamic tissue movements to be quantified, therefore enabling the influence of respiratory mechanics and drive on the genioglossus to be determined (Axel & Dougherty, 1989). Using tagged MRI, dilatory tongue movements have been reported during respiration in healthy adults and OSA patients (Cheng et al 2008;Brown et al 2013;Cheng et al 2014;Cai et al 2016;Kwan et al 2019). Previous studies of the human upper airway indicated that the posterior region of the tongue moves anteriorly during inspiration resulting in airway dilatation (Cheng et al 2008;Kwan et al 2014Kwan et al , 2018.…”
Section: Introductionmentioning
confidence: 99%